KAJIAN PENDAHULUAN FLORISTIK DAN FITOSOSIOLOGI POHON DI PULAU SIMEULEU PROVINSI ACEH - Sadili, Asep; Royyani, M. F.; Agusta, A.; Afandi, I.; Efendy, O.; Ashari, H.; Keim, A. P. (Perhimpunan Biologi Indonesia, 2019)
ABSTRACTSimeuleu island is located in the western part of Sumatera belonging to Aceh Province. Floristic and phytososiological information of vegetation in Simeuleu island is limited and not much study has been conducted, especialy trees species group (diameter ?10 cm). Two study plots were used: one hectare at Kuala Makmur forest and one ha at Alafan forest (100 m × 100 m). Density analisys at Kuala Makmur recorded 329 individuals/ha while at Alafan consisted of 377 individuals/ha (average of 353 individuals/ha). Total basal area at Kuala Makmur 29.48 m2/ha while at Alafan was 44.28 m2/ha (with an average of 36.88 m2/ha). The Shannon-Wiener diversity index (H?) at Kuala Makmur was 2.94 and at Alafan was 2.73 (whit an average H?of 2.84). The total canopy heights of the two study sites as were relatively similar consisting of four strata. Dominant species occurred at Kula Makmur was Shorea atrinervosa (Importance Value, IV=83.55%) and at Alafan was Dipterocarpus grandiflorus (IV=128.06%). Dominant familly at Kuala Makmur was Dipterocarpaceae and at Alafan was Ebenaceae. The distribution of dominant tree species at Kuala Makmur is less prevalent than at Alafan. Keywords: Simeuleu, Aceh, trees structure, species richness, lowland forest.